Diseño de un aplicativo móvil basado en el diagnóstico de gingivitis y periodontitis de la nueva clasificación de enfermedades periodontales (2022)
The new classification of periodontal diseases published in 2018 made multiple changes compared to the 1999 classification for such reason it is believed necessary to develop a mobile tool that will facilitate the diagnostic process in clinical practice.